2015
DOI: 10.3324/haematol.2015.126110
|View full text |Cite
|
Sign up to set email alerts
|

Concomitant systemic and central nervous system non-Hodgkin lymphoma: the role of consolidation in terms of high dose therapy and autologous stem cell transplantation. A 60-case retrospective study from LYSA and the LOC network

Abstract: © F e r r a t a S t o r t i F o u n d a t i o nto report on the therapeutic characteristics of these patients as well as on the role of high-dose therapy and autologous stem cell transplantation in these settings. Methods Study designPatients with histologically confirmed diagnosis of nonHodgkin lymphoma (NHL) made between May 2002 and January 2012 with concomitant systemic and neurological involvement were retrieved from the database of the participating centers, from The Lymphoma Study Association (LYSA) dat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
23
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(25 citation statements)
references
References 24 publications
1
23
1
Order By: Relevance
“…Notably, patients who obtain a CR have an excellent outcome and probably will not benefit from additional high dose therapy, especially those patients with a low IPI at start. This challenges the role of consolidation as suggested by the French lymphoma group LYSA, that showed a positive impact of high-dose therapy followed by autologous stem cell transplantation on 3year OS and PFS [12]. However, in our series 7 of 21 patients (33%) received consolidative radiotherapy.…”
Section: Discussioncontrasting
confidence: 68%
See 1 more Smart Citation
“…Notably, patients who obtain a CR have an excellent outcome and probably will not benefit from additional high dose therapy, especially those patients with a low IPI at start. This challenges the role of consolidation as suggested by the French lymphoma group LYSA, that showed a positive impact of high-dose therapy followed by autologous stem cell transplantation on 3year OS and PFS [12]. However, in our series 7 of 21 patients (33%) received consolidative radiotherapy.…”
Section: Discussioncontrasting
confidence: 68%
“…Given its rarity, data on treatment for sysCNS B-NHL are sparse and there is no established standard of care. Recent data from two studies suggest a beneficial effect of intensive chemotherapy followed by ASCT [12,13]. In both studies, ASCT was only offered to patients in complete remission (CR) (31%-50%).…”
Section: Introductionmentioning
confidence: 99%
“…Few reports have concentrated on these patients. A French group recently published the outcomes of 60 heterogeneously‐treated patients with SCNSL at time of diagnosis (90% DLBCL) and reported a 3‐year PFS of 42% and OS 44% (Damaj et al , ): in the present study the 5‐year PFS was 50% and 5‐year OS 75%. In the French study, >50% of patients were initially treated with R‐CHOP + HD MTX + Ara‐C.…”
Section: Discussionsupporting
confidence: 51%
“…An early study in 24 patients receiving ASCT after CNS relapse of lymphoma showed disappointing results, with only 4 long-term survivors amongst transplant recipients (van Besien et al, 1998). More recently, encouraging results have been demonstrated in patients transplanted in first CR (Cote et al, 2012) and in first or second CR (Ferreri et al, 2014;Chen et al, 2014;Oh et al, 2015;Ferreri et al, 2015b;Damaj et al, 2015;Korfel et al, 2013;Doorduyn et al, 2012). The Centre for Blood and Bone Marrow Transplant Research group recently published data suggesting that outcomes following ASCT were similar in NHL patients with prior CNS involvement and a risk-matched cohort of patients without prior CNS disease, and suggested that high-dose therapy could overcome the adverse impact of this presentation in patients reaching transplant.…”
Section: Discussionmentioning
confidence: 99%
“…Our findings were consistent with other investigators who have reported markedly improved OS among those with responsive disease who ultimately proceeded to ASCT in retrospective series. (Maziarz et al , ; Damaj et al , ) Three prospective studies have evaluated ASCT in SCNSL. Ferreri et al () treated 38 patients with aggressive B‐cell lymphoma and CNS involvement (16 at initial lymphoma presentation).…”
Section: Characteristics Of Patients At Cns Involvement; Cns‐directedmentioning
confidence: 99%